Dampak Ekowisata Danau Rayo Terhadap UMKM Di Desa Sungai Jernih Kecamatan Rupit Kabupaten Musi Rawas Utara - Nusyirwan Nusyirwan; Titin Agustin Nengsih; Ahmad Syukron Prasaja (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Ecotourism is an option to introduce a naturally maintained environment, as well as an area for tourist visits and environmental development based on nature maintenance and conservation. In the process of building and developing ecotourism, tourism activities carried out can have both positive and negative impacts, especially if they are in populated areas. This research was conducted at Lake Rayo Ecotourism, Sungai Jernih Village, Rupit District, North Musi Rawas Regency. This research uses a qualitative approach with in-depth interview data collection techniques and is supported by literature study. This research aims to determine the condition of Lake Rayo Ecotourism, its management and development efforts and the impact of the existence of Lake Rayo Ecotourism on MSMEs in the surrounding community. The results of the research show that ecotourism conditions are in accordance with ecotourism destination standards, where "something to see" is fulfilled, namely special objects and attractions that can be seen, such as unspoiled natural beauty, surrounding flora and fauna, "something to do" and the availability of facilities such as support for visitors to carry out various activities such as boat trips, fishing, photo spots, prayer rooms, tracking and "something to buy" namely the availability of facilities for shopping such as buying food at traders. Efforts to manage and develop Lake Rayo Ecotourism with community involvement/participation are carried out independently, such as: maintenance and repair, creating and adding photo spots, planting and planting, guarding, supervising and protecting the forest from illegal logging. The socio-economic impact that occurs shows a positive impact, namely increasing income for the community and providing business opportunities for the surrounding community through tourism.